Pemberdayaan Ekonomi Nelayan Melalui Budidaya Tiram Terpadu di Desa Kartika Jaya - Niam, Sufa’ah Hurumun; Satsya Yoga Baswara; Ali, Noor Faqih Udin; Ardyansyah, Faisal; Arief, Sandy; Widhiastuti, Ratieh; Saputro, Moh.Eko; Audita, Audy (Yayasan Kawanad, 2025)
Kartika Jaya Village, Patebon Subdistrict, Kendal Regency, has significant oyster aquaculture potential, yet the cultivation practices remain traditional and unstructured. This community service program aimed to enhance technical skills in oyster farming and strengthen the fishermen’s institution through organizational structuring and formal legalization. Training focused on integrated farming techniques, water quality management, as well as business management and digital marketing. Evaluation results showed participants’ understanding increased across all training aspects, with average pre-test to post-test scores improving by 25–40%. Legalization via a Village Government Decree provided access to government assistance and expanded market reach. The program demonstrates that combining technical training with institutional strengthening is an effective strategy to enhance productivity, fishermen’s welfare, and sustainable coastal economic development.